Efek Konseling Gizi Terhadap Pengetahuan Dan Kepatuhan Pembatasan Intake Cairan Pada Pasien Chronic Kidney Disease (CKD) Di Rsud Abdul Wahab Sjahranie Samarinda - Maulida Ulfah; Yuniarti Yuniarti; Arintina Rahayuni (JURNAL NUTRISIA, 2018)
Background:Between 8 to 10% of the adult population suffers kidney damage and every year millions of people die from complications related to CKD. Fluidintake restrictions is the most difficult aspect to adhere, in RSUD Sukoharjo 45,16% who do not adherence of fluid intake restrictions. Based on the results of research in RSUD Sukoharjo as much as 58,06% patients have less knowledge of fluid intake restrictions.Objective: Know the effects of nutrition counseling to knowledge and adherence of fluid intake restrictions on CKD patients in RSUD Abdul Wahab Sjahranie Samarinda.Methods:The type of research was quasi experiment, using pre-post test control group design. Total research subjects were 15 people treatment and 15 control people. Data analysis used to know the difference using different test.Results:There was a significant difference in knowledge of fluid intake restrictionsbefore and after nutritional counseling using leaflets p <0,05 (p = 0,001). There was a significant difference in adherence of fluid intake restrictionsbefore and after nutritional counseling using leaflets p <0,001 (p=0,000). There was a significant difference in knowledge of fluid intakerestrictions before and after nutrition counseling between treatment group and control group p <0,05 (p = 0,006). There was no significant difference in adherence of fluid intakerestrictions before and after nutrition counseling between treatment group and control group p> 0,05 (p = 0,109).Conclusion:Nutrition counseling can improve the knowledge and adherence of fluid intake restrictions in CKD patients undergoing Hemodialysis significantly